Pengaruh Pemberian Larutan KNO3 terhadap Pematahan Dormansi Benih Sirsak - baehaqi, eko; palupi, tantri; asnawati, asnawati (Jurnal Sains Pertanian Equator, 2014)
THE EFFECT OF KNO3 TREATMENT ON SEED DORMANCY BREAKING OF SOURSOP By Eko Baehaqi1) Tantri Palupi2) Asnawati2) 1) Student 2) The Lecturers at Faculty of Agriculture University of Tanjungpura ABSTRAK The Soursop seed is the dormant seed which begins to germinate in 20-30 days after planting, that need an effort to quicken the germination. The reseach is aimed to find the concentration and the length of the submersion using the proper KNO3 soluble to break the soursop seed dormancy. The reseach uses the Complete Random Plan (CRP) method in the factorial with two factors. The First factor is the KNO3 concentration, that is k0= (0%), k1= (1,5%), k2= (3%), k3= (4,5%), and k4= (6%). The second factor is the length of the submersion, that is w1= (12 hours), w2= (24 hours), w3= (36 hours). The reseach consists of fifteen treatments with three repeatations. Every repeatations uses twenty-five seeds. Total obtained is 45 experimental units. The result of the reseach indicates that the giving of the KNO3 soluble to concentration 0%, 1,5%, 3%, 4,5%, and 6% with the length of submersion 12 hours, 24 hours and 36 hours influence unreallity to all variables of the observation. The highest capacity of the germination is on concentration of K4 (6%) and the submersion lenght of 12 hours for 45,33%. Keywords : Consentration KNO3,Dormancy, Soursop Seed